EFFECTS OF PLYOMETRIC TRAINING IN SAND OR RIGID SURFACE ON PHYSICAL-PERFORMANCE RESPONSES AND TESTOSTERONE CONCENTRATION IN FOOTBALL PLAYERS - Muthana Layth Hatem (Proximus Journal Publishing, 2024)
This study aimed to assess the effects of 8 weeks of plyometric training (PT) conducted on sand or a rigid court surface on physical-performance responses and testosterone concentration in football players.
Keywords: surface; assess; effects